Efektifitas Video Edukasi Pembuatan Mpasi 4 Bintang Terhadap Pengetahuan, Sikap Dan Keterampilan Orang Tua Dalam Pencegahan Stunting Pada Balita - Ressa Andriyani Utami; Ernawati; Dameria Br Saragih (STIKes MERCUBAKTIJAYA, 2023)
Stunting is a national problem related to chronic malnutrition which occurs due to multifactors including nutritionalintake, nutritional parenting, genetics, infectious diseases and hygiene. Currently, breakthrough interventions andreal action are needed to overcome editing problems. This research aims to determine the effectiveness of theeducational video for making the MPASI 4 Star menu on the knowledge, attitudes and skills of parents in preventingstunting in toddlers. The research design used is quantitative, quasi-experimental research using a one group pretestposttest design approach. This research was conducted on parents of toddlers in DKI Jakarta with a sample size of 44respondents. The results showed that there was a significant difference in knowledge before and after the intervention(p value 0.000), there was a significant difference in attitudes before and after the intervention (p value 0.000), therewas a significant difference in skills before and after the intervention (p value 0.000 ). It is hoped that this researchcan be an alternative action in the form of education via video for parents to overcome stunting in toddlers and todevelop care, further research can be carried out regarding interventions to deal with stunting.